Quality of Life and Physical Function in Older Patients on Dialysis: A Comparison of Assisted Peritoneal Dialysis with Hemodialysis - Iyasere, Osasuyi U. (Clin J Am Soc Nephrol, 2016)
BACKGROUND AND OBJECTIVES: In-center hemodialysis (HD) is often the default dialysis modality for older patients. Few centers use assisted peritoneal dialysis (PD), which enables treatment at home. This observational study compared quality of life (QoL) and physical function between older patients on assisted PD and HD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Patients on assisted PD who were >60 years old and on dialysis for >3 months were recruited and matched to patients on HD (needing hospital transport) by age, sex, diabetes, dialysis vintage, ethnicity, and index of deprivation. Frailty was assessed using the Clinical Frailty Scale. QoL assessments included Hospital Anxiety and Depression Scale (HADS), Short Form-12, Palliative Outcomes Symptom Scale (renal), Illness Intrusiveness Rating Scale, and Renal Treatment Satisfaction Questionnaire (RTSQ). Physical function was evaluated by Barthel Score and timed up and go test. RESULTS: In total, 251 patients (129 PD and 122 HD) were recruited. In unadjusted analysis, patients on assisted PD had a higher prevalence of possible depression (HADS>8; PD=38.8%; HD=23.8%; P=0.05) and higher HADS depression score (median: PD=6; HD=5; P=0.05) but higher RTSQ scores (median: PD=55; HD=51; P<0.01). In a generalized linear regression model adjusting for age, sex, comorbidity, dialysis vintage, and frailty, assisted PD continued to be associated with higher RTSQ scores (P=0.04) but not with other QoL measures. CONCLUSIONS: There are no differences in measures of QoL and physical function between older patients on assisted PD and comparable patients on HD, except for treatment satisfaction, which is higher in patients on PD. Assisted PD should be considered as an alternative to HD for older patients, allowing them to make their preferred choices.